Effect of Boron on Growth and Seed Yield of Pea Cultivars - Ullah, Izhar; DİREK, Mithat; Chamidah, Dina (Journal of Natural Sciences and Learning, 2024)
An experiment was conducted to know the “Effect of boron on growth and seed yield of pea cultivars” under the agro climatic conditions of Palosi Peshawar at the Horticulture Research Farm, The University of Agriculture Peshawar, during 2022. Experiment was laid out in randomized complete block design with split plot arrangement and replicated three times. The experiment consisted of two factors: First factor was different levels of boron, control, 0.50%, 0.75%, 1.0 %, and boron were added to the main plot, while the other was the pea cultivars Climax, Leena Pak, and Meteor, which were planted in the sub-plot. Different pea cultivars and the foliar application of boron both have a significant impact on pea growth, yield, and seed production. The number of primary branches per plant (13.1), the number of leaves per plant (120.8), the height of the plant (103.5 cm), number of pods per plant (16.6), the length of pod (11.1 cm), the diameter of pod (13.8 mm), number of seeds per pod (10.3), seed yield per plant (160.5), root fresh weight (4.6 g) and the total yield per hectare were all significantly increased by foliar spray of boron. According to the research, foliar application of boron should be applied at a rate of 0.75 % for better growth and production. Pea cultivar Climax should be grown under the agro climatic conditions Peshawar. Keywords: Boron, growth and seed yield, pea cultivars.